Investigation The Effect of Pfizer , AstraZeneca , and Sinopharm Vaccines Against SARS-CoV-2 in Iraq Using Cluster of Differentiation 4 (CD4 ) and Vitamin D3 - Ibraheem, Zoubaida Kh.; AL-azzawy, Raghad H. (Iraqi Journal of Science, 2023)
The research aimed to study the vaccination efficiency against the emerging virus SARS-CoV-2, which includes Pfizer, AstraZeneca and Sinopharm vaccines that are used exclusively in Iraq, by measuring the level of immune cells CD4+ as well as vitamin D3 using ELISA technology. Taking serums were taken from vaccinated individuals: 20 uninfected before individuals who got a vaccination and 20 people with prior infections who had the vaccine (for each type of the three vaccines). Samples were collected 21 days following the second dose as well as 3 to 6 months thereafter. The results showed that the most effective vaccine was AstraZeneca and the results of T-cells were the highest compared to Pfizer and Sinopharm.